التكنولوجيا المالية كآلية لمنهوض بالابتكاارت المالية الإسلامية دارسة عمى ضوء تجارب دولية - جـامع مريـم (جامعة البليدة2؛كلية العلوم الاقتصادية العلوم التجارية وعلوم التسيير, 2025)
يهدف هذا البحث لمعالجة موضوع الابتكاارت المالية الإسلامية والتعرف عمى تقنيات التكنولوجيا المالية الداعمة لها. و تازمنا وانفتاح المجتمعات عمى التمويل الإسلامي الأمر الذي يضع المؤسسات المالية الإسلامية أمام رهان استخدام التقنيات التي يمكن من خلالها دعم ابتكاارتها وتسهيل نشرها والتعامل بها، فقد استخدمت التكنولوجيا المالية لتطوير مختمف المنتجات و نتج عن ذلك من منصات التمويل ،المالية الإسلامية وتحويمها لابتكاارت تتسم بالرقمنة الجماعي، منصات الوقف، الصكوك الذكية، ومنصات خاصة بزكاة المال. ي ات المالية الإسلامية و ح هذا البحث الأدبيات المتعمقة بالابتكار ّ وض علاقتها بتطبيقات في المممكة العربية السعودية وماليزيا كونهما تركازن عمى تبني تقنيات متطورة ،التكنولوجيا المالية في القطاع المالي الإسلامي، كما تسمط الدارسة الضوء كذلك عمى جهود الجازئر في تطبيق قوانين الصيرفة الإسلامية واستخدام تقنيات التكنولوجيا المالية، إضافة إلى التحديات التي تواجه تبني تمك الابت. وآليات تطوير التكنولوجيا المالية بها ، ائري ات في النظام المالي الجز كار وخمصت الدارسة إلى أن التكنولوجيا المالية تدعم الابتكاارت المالية الإسلامية وتساهم في توسعها وانتشارها وزيادة تنافسيتها، إضافة إلى أن الجازئر قد خطت خطوات واضحة في استخدام ات واليد العاممة المؤهمة وتفعيل غم ذلك فإنه من الضروري تطوير الخبر ولكن ور ، التقنيات المالية الأمن السيبارني، ووضع قوانين تخفف العارقيل الإدارية في إنشاء المؤسسات المالية التقنية. الكممات المفتاحية: ابتكاارت مالية إسلامية، تكنولوجيا مالية، بموكتشين، أمن سيبارني، اThe aim of this research is to address the subject of Islamic financial innovation as well as identifying methods that support its development, mainly through the use of financial technology. In parallel with the oppeness of societies to Islamic finance and the increase in number of islamic financial services clients and fintech users, both, Islamic financial institutions was driven to integrate mechanisms that promote the implementation, the use and the broad reach of their financial products, such as :crowd-funding platforms, waqf platforms, smart sukuk platforms, and zakat platforms. This research focuses on the Islamic Fintech and its innovations and development mainly in Kingdom of Saoudi Arabia(KSA) and Malysia, both countries assure to adapt an ecosystem that promotes Islamic fintech through the integration of advanced intormation technologies in the Islamic financial sector. The study also highlights the efforts of Algerian banking system on applying Islamic banking regulations and implementing financial technologies. The study concluded that fintech promotes Islamic Financial innovation, and contribute to its growth, expension and increased competitiveness, and that the Algerien Banking and finance sector is taking steady steps in integrating fintech, in parallel with forming and training qualified human resources that has the necessary skills and expertise, along with establishing efficiente cybersecurity measures, and effective regulations to deminish administrative barriers that obstruct the establishment of successful fintech institutions. Keywords: islamic financial innovation, financial technology, blockchain, cybersecurity, Algeria. لجازئر.
Keywords: ابتكاارت مالية إسلامية; تكنولوجيا مالية; أمن سيبارني